Implementasi Simple Network Management Protocol (SNMP) dalam Perancangan Sistem Monitoring Jaringan Berbasis Web (Studi Kasus: PT BFI Finance Indonesia Tbk, Cisauk) - Muhammad Agus Saputra; Ari Syaripudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Network monitoring at BFI Finance Cisauk is still done manually by tracking directly on devices in the company environment. This has an impact on the time efficiency used by the Network Operation Center (NOC) because it has to check the devices one by one. In addition, with so many devices managed, the problem is even more complex, because NOCs have difficulty monitoring existing devices. On the other hand, the absence of a system that monitors the condition of network devices at BFI Finance Ciasuk slightly interferes with the company's operational continuity because NOC still relies on conventional methods, namely waiting for reports from clients so that if there is a problem with devices such as routers, switches and server handlers are not fast. For this reason, a Network Management System is needed, where the standard used is (SNMP) Simple Network Management Protocol. In the construction of a software, system failures often occur, errors in the development are often called software crisis which basically the software built is not in accordance with the goals to be achieved. To avoid this software crisis there are several methods in creating a software where in this study the author used the waterfall method. The result of this research is that the network monitoring process can be carried out in real time so that work becomes more effective, fast, precise and efficient.